Maternal vitamin B12 status in early pregnancy and its association with birth outcomes in Canadian mother–newborn Dyads. Issue 12 (28th December 2021) - Tan, Amy; Sinclair, Graham; Mattman, Andre; Vallance, Hilary D.; Lamers, Yvonne
Abstract: Vitamin B12 (B12 ) is a co-enzyme essential for fetal growth and development. Lower maternal B12 status has been associated with preterm birth (<37 gestational weeks) and low birth weight (<2500 g), which are linked to morbidity and mortality across the lifespan. In Canada, 17–25 % of women in early pregnancy had a serum total B12 concentration <148 pmol/l and maternal total B12 concentration decreased throughout pregnancy. This study aimed to determine the association between maternal B12 status and birth outcomes in Canadian mother–newborn dyads. A secondary analysis of 709 mother–newborn dyads in British Columbia (BC), Canada, was conducted. Bio-banked first- ( n 656) and second-trimester ( n 709) maternal serum samples of apparently healthy South Asian (50 %) and European (50 %) women from the BC Prenatal Genetic Screening Program were quantified for B12 biomarkers (total B12, holotranscobalamin (holoTC), methylmalonic acid (MMA) and total homocysteine (tHcy)). Obstetric history and birth outcome data were obtained from the BC Perinatal Data Registry. All associations were determined using multiple linear regression. Maternal serum total B12, holoTC, MMA and tHcy had a mean weekly decrease of 3·64 pmol/l, 1·04 pmol/l, 1·44 nmol/l and 0·104 μmol/l, respectively ( P < 0·001). Despite a total B12 concentration <148 pmol/l among 20–25 % of the women, maternal B12 biomarker concentrations were not associated with birth weight z -score, head circumference z -score and gestational age at birth ( P > 0·05). Additional research in women at high risk of adverse birth outcomes and the association between maternal B12 status and functional, for example, cognitive, outcomes is needed.